Public participation in environmental impact assessment processes of forest operations in Peninsular Malaysia - Othman, Mohd Shahwahid; M. S., Farah (Forestry Department Peninsular Malaysia, 2011)
This paper elaborates on the benefits of public participation in environmental impact assessment (EIA) processes. The legal requirement of public participation in EIA processes in Malaysia was investigated. Detailed EIA (DEIA) of forest operations has engaged (i) the general public during the formulation of the terms of reference of the DEIA, and when displaying the final report of the DEIA and (ii) the local communities and relevant affected stakeholders during the survey interviewing with village leaders and other affected parties. While public participation in the macro as well as preliminary EIA for forest plantation operations occurred during the interviewing of village heads and local community surveys. The results of local community surveys have highlighted significant roles of the natural forest to households living close to forests and the perceptions of the impacts of forest operations on the environment. There are positive outcomes of public participation in the EIA processes whereby the feedbacks of local community concerns are seen to be incorporated into the licensing contract of the forest operations.